Psychometric properties of Turkish versions of the short video flow scale and short video addiction scale - Türk, Nuri; Yıldırım, Oğuzhan (Journal of Dependence, 2024)
Objective: The aim of this study is to examine the Short Video Flow Scale (SVFS) and the Short Video Addiction Scale (SVAS) in terms of validity and reliability, and adapt them to the Turkish culture. Method: The study was conducted with the survey model. The sample group consisted of 297 high school students selected by convenience sampling method. During the translation process of SVFS and SVAS, the stages recommended by the International Test Commission were taken into account. Results: Reliability analyses of the scales were carried out with the Cronbach’s Alpha reliability coefficient. Reliability coefficient was found to be .87 for SVFS and .82 for SVAS. Item discrimination was examined with item-total score correlation values. In addition, upper and lower 27% groups were created in the data set and the significance level of the difference between the groups was tested. In order to examine the criterion validity of SVFS and SVAS, the Multiple Screen Addiction Scale and the Phubbing Scale were used and the correlations coefficients between the scales were calculated. Correlation coefficients ranged between .54 and .77. CFA technique was used to test the construct validity of SVFS and SVAS. The factor loadings varied between .56 and .76 for SVFS and between .45 and .72 for SVAS. Both SVFS and SVAS had a single-factor structure, which is consistent with their original versions. Conclusion: The Turkish form of SVFS and SVAS can be used to assess attitudes, feelings and behaviors of watching short videos.